2012
DOI: 10.1111/j.1753-4887.2012.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and nutritional significance of virgin argan oil - an edible oil with potential as a functional food

Abstract: This review compiles recently published scientific reports on the bioactive compounds present in virgin argan oil along with their possible beneficial effects on human health, which could justify consideration of this oil as a new functional food. Virgin argan oil is characterized by high levels of linoleic and oleic acids, tocopherols (especially γ-tocopherol), and minor compounds such as sterols, carotenoids, and squalene. The total antioxidant capacity of virgin argan oil is higher than that of other vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 87 publications
3
31
0
Order By: Relevance
“…In addition, the presence of minor bioactive compounds such as sterols, carotenoids, xanthophylls, squalene and CoQ 10 contributes to its antioxidant potential, nutritional value and health properties (Cabrera-Vique, Marfil, Giménez, & Martínez-Augustin, 2012;Charrouf & Guillaume, 2014). Recent studies have shown it to have hypolipidaemic, hypocholesterolaemic, hypoglycaemic and antihypertensive effects as well as a possible role in cancer prevention (Cabrera-Vique et al, 2012;Charrouf & Guillaume, 2014;Cherki, Berrougui, Drissi, Adlouni, & Khalil, 2006;El Monfalouti, Guillaume, Denhez, & Charrouf, 2010;Sour et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, the presence of minor bioactive compounds such as sterols, carotenoids, xanthophylls, squalene and CoQ 10 contributes to its antioxidant potential, nutritional value and health properties (Cabrera-Vique, Marfil, Giménez, & Martínez-Augustin, 2012;Charrouf & Guillaume, 2014). Recent studies have shown it to have hypolipidaemic, hypocholesterolaemic, hypoglycaemic and antihypertensive effects as well as a possible role in cancer prevention (Cabrera-Vique et al, 2012;Charrouf & Guillaume, 2014;Cherki, Berrougui, Drissi, Adlouni, & Khalil, 2006;El Monfalouti, Guillaume, Denhez, & Charrouf, 2010;Sour et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…In addition, the presence of minor bioactive compounds such as sterols, carotenoids, xanthophylls, squalene and CoQ 10 contributes to its antioxidant potential, nutritional value and health properties (Cabrera-Vique, Marfil, Giménez, & Martínez-Augustin, 2012;Charrouf & Guillaume, 2014). Recent studies have shown it to have hypolipidaemic, hypocholesterolaemic, hypoglycaemic and antihypertensive effects as well as a possible role in cancer prevention (Cabrera-Vique et al, 2012;Charrouf & Guillaume, 2014;Cherki, Berrougui, Drissi, Adlouni, & Khalil, 2006;El Monfalouti, Guillaume, Denhez, & Charrouf, 2010;Sour et al, 2012). Among the various components of the Mediterranean diet, much attention has been paid to virgin olive oil, because its consumption is associated with favorable cardiovascular outcomes (Sour et al, 2012); however, some countries, namely those in the Maghreb area, also consume virgin argan oil in the habitual diet, and a growing body of evidence suggests that this edible oil might have healthful effects, mostly as a result of its antioxidant activity, that would reduce the incidence of cardiovascular disease and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[20] The unsaponifiable fractions of argan oil contain about 20% of triterpene alcohols. [12,16,[22][23][24][25][26][27][28][29][30][31][32][33] Cadmium, zinc, iron, potassium, magnesium, and calcium were also extracted from argan oil in trace amounts. The presence of the hydroxyl group at position C3 is inherent and is the key to their biogenic compounds.…”
Section: Chemical Composition and Physicochemical Properties Of Arganmentioning
confidence: 99%
“…Reference [12] [32] [16] [29] [23,24,27] [ 25] Edible Cosmetic [22] RAO UAO [22] SFE Soxhlet [28] TO MO [30] Sample [ www.advancedsciencenews.com www.ejlst.com skin. It provides an outer protective layer, that stops evaporating water from epidermis.…”
Section: Saturated and Unsaturated Fatty Acidsmentioning
confidence: 99%
“…They have high energy value and are highly digestible (Saricicek & Kilic, 2004). Kernel oils of the English and Turkish oak are characterized by high levels of oleic (over 40%) and linoleic (over 30%) acids (Cabrera-Vique, Marfil, Giménez, & Martínez-Augustin, 2012;Petrović, Šobajić, Rakić, Tomić, & Kukić, 2004) and are also valuable source of essential α-linolenic acid (1.8 and 3.7%, respectively) (Petrović et al, 2004). The acorn kernels of these two Quercus species beside nutritional components contain various biologically active compounds (tannins, gallic and ellagic acid, and different galloyl and hexahydroxydiphenoyl derivatives), that contribute to antioxidant properties, which were proven in various test models and comparable with some commercial antioxidants (Rakić, Maletić, Perunović, & Svrzić, 2004;Rakić, Povrenović, Tešević, Simić, & Maletić, 2006;Rakić, Petrović, Kukić, Jadranin, Tešević, Povrenović, & Šiler-Marinković, 2007).…”
mentioning
confidence: 99%